Pengembangan Modul Berdiferensiasi Berbasis Metode Drill untuk Meningkatkan Pemahaman Konsep Siswa Sekolah Dasar pada Operasi Hitung Perkalian dan Pembagian - Oktavia Damayanti; Dyana Wijayanti (Universitas Muhammadiyah Semarang, 2026)
Elementary school students conceptual understanding on multiplication and division operations is still relatively low. We contend that this is convinient to the shortage of learning media that suits students need also the minimal using of effective tecnique. This research was purposelly to established a differentiated module based towards the drill method to rectify students conceptual understanding of multiplication and division. The method was using research also is research and expansion with the ADDIE development model: analysis, design, development, implementation, and evaluation. The subjects this research were grade III students of public elementary schools in Klaten district, Central Java who were grouped into low and medium categories. The yields this reseach was shown that developed module named valid and very valid with a validity score 90% based on material experts and 90,67% according to media experts. Practicality released the criteria of very practical with a student response score of 94.17% and a teacher response of 95%. Additionally, the drill method using developed modul was effective for both groups students.